[Image 65] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Extensive view of the most magnificent scenery near the Giant's Causey in the county of Antrim as see from the rocks looking along the coast they way of the Causeway by Sir Wm Smith 1802.
Keywords: Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Giant's Causeway (Northern Ireland); Antrim (Northern Ireland : County) -- Pictorial works; Landscapes (Representations) 1800-1810